Pengaruh Menonton Drama Korea terhadap Gaya Hidup Remaja Muslim - Yurika Nur Prasetya; Erhamwilda; Enoh Nuroni (Bandung Conference Series: Islamic Education, 2024)
Abstract. This research was conducted on teenagers aged 12-22 years who like Korean dramas with the aim of finding out the effect of watching Korean dramas on teenagers' lifestyles. This research uses a quantitative approach with survey methods which are included in correlation research. The type of sampling used Side Nonprobability with Purposive Sampling technique due to certain considerations, namely teenagers aged 12-22 years who like Korean dramas. The research results show 1) The intensity of teenagers in watching Korean dramas obtained a total percentage of 57.09% in the quite high category. 2) the lifestyle of teenagers who tend to watch Korean dramas gets a total percentage of 62.2% in the high category. 3) the relationship between watching Korean dramas and teenagers' lifestyles obtained a coefficient value of 0.688 with a positive relationship in the strong category between variable X and variable Y. 4) the positive impact of Korean culture is that it provides inspiration and motivation to study abroad, and other impacts is in the Korean education system which can be used as an example to improve the quality and quantity of education in the country. Negative impacts such as procrastination, namely delaying prayer times, neglect of parental duties, and the tendency to watch late at night can be signs of an obsessive tendency towards Korean drama content. Abstrak. Penelitian ini dilakukan kepada remaja berusia 12-22 tahun yang menyukai drama Korea dengan tujuan untuk mengetahui pengaruh menonton drama Korea terhadap gaya hidup remaja. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei yang termasuk ke dalam penelitian korelasi. Jenis pengambilan sampel menggunakan Nonprobability Samping dengan teknik Sampling Purposive karena adanya pertimbangan tertentu yaitu remaja berusia 12-22 tahun yang menyukai drama Korea. Hasil penelitian menunjukan 1) Intensitas remaja dalam menonton drama Korea memperoleh total persentase sebesar 57,09% dengan kategori cukup tinggi. 2) gaya hidup remaja yang kecenderungan menonton drama Korea memperoleh total persentase sebesar 62,2% dengan kategori tinggi. 3) hubungan antara menonton drama Korea terhadap gaya hidup remaja memperoleh nilai koefisien sebesar 0,688 dengan hubungan yang positif dengan kategori kuat antara variabel X dengan variabel Y. 4) dampak positif budaya Korea adalah memberi inspirasi dan motivasi untuk menempuh Pendidikan diluar negeri, dan dampak lainnya adalah dalam sistem Pendidikan di Korea yang bisa dijadikan contoh untuk meningkatkan kualitas dan kuantitas Pendidikan di dalam Negeri. Untuk dampak negatif seperti prokrastinasi yaitu menunda waktu shalat, melalaikan tugas dari orangtua, dan kecenderungan untuk menonton hingga larut malam bisa merupakan tanda adanya kecenderungan obsesif terhadap konten drama Korea tersebut.